Why did they kill? : Cambodia in the shadow of genocide - Hinton, Alexander Laban (Berkeley : University of California Press, 2005)
Of all the horrors human beings perpetrate, genocide stands near the top of the list. Its toll is staggering: well over 100 million dead worldwide. Why Did They Kill? is one of the first anthropological attempts to analyze the origins of genocide. In it, Alexander Hinton focuses on the devastation that took place in Cambodia from April 1975 to January 1979 under the Khmer Rouge in order to explore why mass murder happens and what motivates perpetrators to kill.
Introduction : in the shadow of genocide -- The prison without walls -- A head for an eye : Disproportionate Revenge -- Power, patronage, and suspicion -- In the shade of Pol Pot's umbrella -- The fire without smoke -- The DK social order -- Manufacturing difference -- The dark side of face and honor -- Conclusion : why people kill.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Cambodia -- Politics and government -- 1975-1979.; Political atrocities -- Cambodia; Genocide -- Cambodia; War crimes; War Crimes; Cambodia; Atrocités politiques -- Cambodge; Génocide -- Cambodge; Cambodge -- Politique et gouvernement -- 1975-1979.; Crimes de guerre; HISTORY; SOCIAL SCIENCE -- Anthropology -- Cultural; War crimes; Genocide; Political atrocities; Politics and government; Cambodia; Genocide; Rode Khmer; Binnenlandse conflicten; 1975-1979; 1970s.; anthropological analysis; anthropologists; anthropology; cambodia; cambodian culture; cambodian genocide; cultural knowledge; cultural studies; death toll; execution; genocidal ideologies; history of violence; human motivation; human psychology; human rights; illness; khmer rouge; malnutrition; mass murder; millions dead; nazi regime; nonfiction; origins of genocide; overwork; perceived differences; political movement; political violence; social analysis; southeast asia; starvation; violence; Electronic book